Graphene Multielectrode Arrays as a Versatile Tool for Extracellular Measurements. Issue 12 (3rd April 2017) - Kireev, Dmitry; Seyock, Silke; Lewen, Johannes; Maybeck, Vanessa; Wolfrum, Bernhard; Offenhäusser, Andreas
Abstract : Graphene multielectrode arrays (GMEAs) presented in this work are used for cardio and neuronal extracellular recordings. The advantages of the graphene as a part of the multielectrode arrays are numerous: from a general flexibility and biocompatibility to the unique electronic properties of graphene. The devices used for extensive in vitro studies of a cardiac‐like cell line and cortical neuronal networks show excellent ability to extracellularly detect action potentials with signal to noise ratios in the range of 45 ± 22 for HL‐1 cells and 48 ± 26 for spontaneous bursting/spiking neuronal activity. Complex neuronal bursting activity patterns as well as a variety of characteristic shapes of HL‐1 action potentials are recorded with the GMEAs. This paper illustrates that the potential applications of the GMEAs in biological and medical research are still numerous and diverse. Abstract : Graphene multielectrode arrays (GMEAS), reported in this work exhibit excellent ability to record electrophysiological signals. Cardiac‐like cell activity as well as complex neuronal activity can be recorded with the arrays of graphene‐based electrodes. Low noise performance, the corresponding large signal to noise ratio, and excellent long term in vitro stability place the GMEAs at the forefront of electrophysiological tools.